2008
DOI: 10.1088/1126-6708/2008/10/077
|View full text |Cite
|
Sign up to set email alerts
|

U(1) mediation of flux supersymmetry breaking

Abstract: We study the mediation of supersymmetry breaking triggered by background fluxes in Type II string compactifications with N = 1 supersymmetry. The mediation arises due to an U(1) vector multiplet coupling to both a hidden supersymmetry breaking flux sector and a visible D-brane sector. The required internal manifolds can be constructed by non-Kähler resolutions of singular Calabi-Yau manifolds. The effective action encoding the U(1) coupling is then determined in terms of the global topological properties of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 134 publications
0
42
0
Order By: Relevance
“…It is worth noting that our proposal differs slightly in its implementation of the differential structure from similar setups such as presented in [70,74,75]. Once the first relation in (3.13) is introduced the natural complement relation involves a set of non-closed 5-forms rather than the 3-forms we have introduced.…”
Section: Jhep12(2011)004mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that our proposal differs slightly in its implementation of the differential structure from similar setups such as presented in [70,74,75]. Once the first relation in (3.13) is introduced the natural complement relation involves a set of non-closed 5-forms rather than the 3-forms we have introduced.…”
Section: Jhep12(2011)004mentioning
confidence: 99%
“…in [74]. These R-R gauge bosons become massive by 'eating' an R-R axion which sits with the non-Calabi-Yau deformations in the same supermultipet.…”
Section: Jhep12(2011)004mentioning
confidence: 99%
“…The possibility of having hidden U(1) gauge symmetries has also motivated interesting applications in the context of supersymmetric models. For instance, it has been suggested that hidden U(1)'s can lead to a possible mechanism for mediating SUSY breaking to the visible sector in a flavor independent way [11][12][13][14]. Also, mixing of MSSM neutralinos with hidden U(1) gauginos can be a relevant signature at the LHC [15][16][17][18].…”
Section: Jhep09(2011)110mentioning
confidence: 99%
“…by extending the non-compact setups of [292] to D5-branes on vanishing two-cycles in compact Calabi-Yau orientifolds. A different application is provided by explicit GUT model building in Type IIB compactifications, where it would be of particular importance to include matter from intersecting D5-branes using similar techniques as developed for intersecting D7-branes [293,294] 2 . Furthermore, the effective action allows also some general conclusions about moduli stabilization.…”
Section: The Su(3)-structure On the Manifoldẑmentioning
confidence: 99%